Coxiella burnetii DNA detected in domestic ruminants and wildlife from Portugal - Cumbassá, A. (2019)
Coxiella burnetii is the etiological agent of Q fever or Coxiellosis, a zoonosis mainly affecting domestic ruminants. Information on the population structure and epidemiology of C. burnetii in animals is scarce in Portugal. Evidence of C. burnetti infection was sought in domestic, wild and captive animals based on the detection of bacterial DNA. Tissue samples from 152 domestic animals (cattle = 24, goats = 51, sheep = 76 and swine = 1), 55 wild carnivores (Egyptian mongoose = 45, red fox = 4, common genet = 3, weasel = 2 and European badger = 1) and 22 zoo animals (antelopes = 15, impala = 1; rhinoceros = 1, deer = 2, zebras = 2 and giraffe = 1) were screened by nested-touchdown PCR. Cloacae swabs from 19 griffon vultures were also analysed. Among the domestic ruminants, goats presented the highest prevalence of infection (23.53%), followed by cattle, (20.83%) and sheep (10.53%). C. burnetii DNA was also detected in five Egyptian mongooses and two antelopes and one giraffe. Using a 6-locus multiple-locus variable-number tandem repeat analysis (MLVA-6) six complete genotypes, T, I and CM and the first reported CN, CO and CP, were identified, respectively, in small ruminants and Egyptian mongooses. Clustering analysis of genotypes exposed four distinct groups, according to detection source, enlightening an apparent association between C. burnetii genotype and host.